Determining the prevalence of tuberculosis infection in populations with non-specific tuberculin sensitivity - ten Dam, H. G. (1980)
In tropical countries, where there is generally a high prevalence of non-specific sensitivity, the tuberculin test is inadequate for detecting tuberculosis infection. A method is proposed by which the prevalence of infection in the population can be determined under such circumstances thus making possible meaningful epidemiological surveillance of the disease. This method compares levels of tuberculin sensitivity in individuals before and after BCG vaccination. If BCG vaccination fails to produce an increase in tuberculin sensitivity, the individual must have been infected with human or bovine tubercle bacilli.